The team as a secure base: Promoting resilience and competence in child and family social work. (December 2017) - Biggart, Laura; Ward, Emma; Cook, Laura; Schofield, Gillian
Abstract: This paper outlines research findings on the relevance of the Secure Base model (Schofield & Beek, 2014) for developing supportive teams in child and family social work. When the social work team functions as a secure base, this can help workers cope with the emotional demands of the role. The concept of the secure base comes from attachment theory (Bowlby, 1969) in which our relationships with significant others, who are available, sensitive to our needs and reliable, provide us with a secure base to return to when life is stressful and provide us with comforting internal mental models when we are physically away from them. This 'secure base for exploration' reduces anxiety and enables us to engage with the world, consider the internal world of others (empathy) and remain resilient when life is stressful. Using data from 52 phone interviews with child and family social workers across eight local authorities in the UK, we show how the Secure Base model has relevance for emotion regulation and resilience for child and family social workers. Data were analysed using Theoretical Thematic Analysis (Braun & Clarke, 2006). In the context of the emotional demands of social work, our data indicate that the supervisors and teams provide a work related secure base across five dimensions by behaving in ways which instil these beliefs: Availability - 'People are there for me'; Sensitivity - 'My feelings are manageable'; Acceptance - I don't always have to be strong'; Cooperation - 'I can work with others to find a solution'; Team belonging - 'I am valued and I belong'. Implications for practice are proposed to help supervisors and team members reflect on beliefs and behaviours which can help provide a secure base for their teams. Highlights: Emotion regulation is important for social work practice. Supervisors and teams provide essential social support to help regulate emotions. The five dimensions of our Secure Base model help emotion regulation but also build self-esteem and self-efficacy. Secure base team: availability, sensitivity, acceptance, cooperation, membership.